Cucurbitacin B Inhibits Cell Proliferation by Regulating X-Inactive Specific Transcript Expression in Tongue Cancer - Tao, Boqiang; Wang, Dongxu; Yang, Shuo; Liu, Yingkun; Wu, Han; Li, Zhanjun; Chang, Lu; Yang, Zhijing; Liu, Weiwei (Frontiers in Oncology, 2021)
Cucurbitacin B (CuB), a natural product, has anti-tumor effects on various cancers. In order to investigate the expression of long non-coding RNAs (lncRNA), we carried out RNA sequencing (RNA-seq) and quantitative PCR (qPCR). The data indicated that CAL27 and SCC9 tongue squamous cell carcinoma (TSCC) cells had reduced expression of X-inactive specific transcript (XIST) after CuB treatment. Moreover, our results showed increased expression of XIST in human tongue cancer. In this study, CuB treatment inhibited proliferation, migration and invasion of SCC9 cells, and induced cellular apoptosis. Interestingly, knockdown of XIST led to inhibition of cell proliferation and induced apoptosis in vitro. In addition, reduced expression of XIST suppressed cell migration and invasion. MicroRNA 29b (miR-29b) was identified as a direct target of XIST. Previous reports indicated that miR-29b regulates p53 protein. Our results suggest that increased expression of miR-29b induces cell apoptosis through p53 protein. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (CRISPR/Cas9) system validated the role of XIST knockout in tumor development in vivo. Together, these results suggest that CuB exerts significant anti-cancer activity by regulating expression of XIST via miR-29b.